Smarter crime control : a guide to a safer future for citizens, communities, and politicians - Waller, Irvin (Rowman & Littlefield, 2014)
In the wake of headline-grabbing mass murders and other controversial crimes, public officials and communities alike are searching for ways to best deal with crime - both minor and major. Here, Waller highlights best practices as shown by scores of studies, underscores the need for better preventions, and details the best innovations in the reduction of crime and violence of all kinds.